Bobble-Head Doll Syndrome Treated Surgically - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2005)
A case of a 4-year-old child with bobble-head doll syndrome (BHDS) caused by a suprasellar arachnoid cyst and successfully treated by endoscopic cystovenriculostomy is reported from Medisch Centrum Haaglanden, The Hague; and Academical Hospital Nijmegen, The Netherlands.